2015
DOI: 10.1002/bmc.3435
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of polygalasaponin F in rat plasma using liquid chromatography–tandem mass spectrometry and its pharmacokinetics application

Abstract: A rapid and highly selective liquid chromatography-tandem mass spectrometric (LC-MS/MS) method for determination of polygalasaponin F (PF) in rat plasma was developed and validated. The chromatographic separation was achieved on a reverse-phase Zorbax SB-C18 column (150 × 4.6 mm, 5 µm), using 2 mm ammonium acetate (pH adjusted to 6.0 with acetic acid) and acetonitrile (25:75, v/v) as a mobile phase at 30 °C. MS/MS detection was performed using an electrospray ionization operating in positive ion multiple react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Polygala (P.) japonica herba, a traditional Chinese herb, has been used as an expectorant, antitussive, antibacterial, and ataractic agent (Zhang et al 1996). It is widely used in China to treat acute bronchitis, pharyngitis, pneumonia, amygdalitis, and respiratory tract infections in children (Zhou et al 2015). The compounds isolated from P. japonica so far mainly include saponins, flavonoids, xanthones, polysaccharides, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polygala (P.) japonica herba, a traditional Chinese herb, has been used as an expectorant, antitussive, antibacterial, and ataractic agent (Zhang et al 1996). It is widely used in China to treat acute bronchitis, pharyngitis, pneumonia, amygdalitis, and respiratory tract infections in children (Zhou et al 2015). The compounds isolated from P. japonica so far mainly include saponins, flavonoids, xanthones, polysaccharides, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Polygalasaponin F (PSF, C 53 H 86 O 23 , Fig. 1) is a triterpenoid saponin and is also one of the major active constituents of P. japonica used for the quality control of the medicine (Zhou et al 2015). Previous research has reported that PSF has anti-inflammatory effects and its mechanism is associated with the NF-κB signaling pathway (Wei et al 2014;Yan et al 2015;Wang et al 2008).…”
Section: Introductionmentioning
confidence: 99%